ANALISIS PERKEMBANGAN KONSEPSI SISWA MENGENAI STRUKTUR ATOM DI SMA ADABIAH PADANG - Zonalia Fitriza; Latisma DJ; Mawardi Mawardi (PAKAR Pendidikan, 2015)
The examination result of X grade students in SMA Adabiah Padang shows that most of the students comprehend less than 60% of the learning material about atom. It will impact to the learning in the higher grade, therefore, a study held to know the conceptual development of students. It was qualitative descriptive which explorative and cross sectional approach. The instrument is open ended questions which gave to 204 students to know their conception about atom. Their conceptions tend developed in the electron configuration of atom, electron configuration of ion, determination of period and group of atom. In Addition, majority of students had the correct concept about the basic particles of atom. Meanwhile, the concept about atom and atomic model did not change significantly. Most of them did not understand in the concept of wave mechanic atomic model.